2014
DOI: 10.1111/ina.12164
|View full text |Cite
|
Sign up to set email alerts
|

Polycyclic aromatic hydrocarbons: levels and phase distributions in preschool microenvironment

Abstract: This work aims to characterize levels and phase distribution of polycyclic aromatic hydrocarbons (PAHs) in indoor air of preschool environment and to assess the impact of outdoor PAH emissions to indoor environment. Gaseous and particulate (PM 1 and PM 2.5 ) PAHs (16 USEPA priority pollutants, plus dibenzo [a,l] This study fills a gap providing information on levels and phase distribution (gas, and PM 1 and PM 2.5 -bound) of polycyclic aromatic hydrocarbon (PAHs) in preschool educational settings. Despite the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 52 publications
0
11
1
Order By: Relevance
“…At both preschools, sampling campaigns were performed over 24-hr; however, the inclusion of the periods without stu-dents and their activities such as during nights when classrooms were empty and all windows and doors were closed may contribute to lower mean levels of PM 2.5 . The results obtained in this study were also lower than concentrations reported by,Oliveira et al (2015bOliveira et al ( , 2015c, andRawi et al (2015), which may be attributed to varying sam-pling strategies (8-or 24hr sampling periods), different seasonal and/or meteorological condi-tions and to various environmental characteristics. The findings of this study are in agreement with those ofMadureira et al (2012), who also detected negative correlations between RH and CO 2 levels with PM 10 , PM 2.5 , and PM 1 in indoor air of Portuguese primary schools.…”
contrasting
confidence: 72%
See 2 more Smart Citations
“…At both preschools, sampling campaigns were performed over 24-hr; however, the inclusion of the periods without stu-dents and their activities such as during nights when classrooms were empty and all windows and doors were closed may contribute to lower mean levels of PM 2.5 . The results obtained in this study were also lower than concentrations reported by,Oliveira et al (2015bOliveira et al ( , 2015c, andRawi et al (2015), which may be attributed to varying sam-pling strategies (8-or 24hr sampling periods), different seasonal and/or meteorological condi-tions and to various environmental characteristics. The findings of this study are in agreement with those ofMadureira et al (2012), who also detected negative correlations between RH and CO 2 levels with PM 10 , PM 2.5 , and PM 1 in indoor air of Portuguese primary schools.…”
contrasting
confidence: 72%
“…Thus, it would seem that children exposure in preschools may vary from older students' envir-onments. During the last years, some studies con-cerning exposure of young children, that is, less than 5 years, to indoor air pollutants at educa-tional microenvironments were reported for: 1) nurseries (Branco et al, 2014(Branco et al, , 2015a(Branco et al, , 2015bNunes et al, 2015Nunes et al, , 2016, 2) day-care centers and kindergartens (Araújo-Martins et al, 2014;Carreiro-Martins et al, 2014;Cyprowski et al, 2013;Gładyszewska-Fiedoruk, 2013;Yang et al, 2009), and 3) preschools (Fonseca et al, 2014;Latif et al, 2014;Oliveira et al, 2015aOliveira et al, , 2015bOliveira et al, , 2015cOliveira et al, , 2016aOliveira et al, , 2016bOliveira et al, , 2016cSlezakova et al, 2015;Rawi et al, 2015;Vassura et al, 2015;Wichmann et al, 2010;Yoon et al, 2011). Some of these investigations mainly focused on ventilation and/ or carbon dioxide (CO 2 ) levels as a global IAQ indicator (Branco et al, 2015a;Carreiro-Martins et al, 2014;Gładyszewska-Fiedoruk, 2013;Latif et al, 2014;.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, a number of investigators determined PAH levels in schools, but the current understanding is far from compre-hensive. Further, most of the existing knowledge originates from the studies conducted in environ-ments for 6-10/11-year-old students (i.e., primary/ elementary levels of education) (Alves et al, 2014;Carpenter & Bushkin-Bedient, 2013;Cirillo et al, 2006;Jovanović et al, 2014;Jyethi et al, 2014;Krugly et al, 2014;Moshammer & Neuberger, 2003;Romagnoli et al, 2014;Ruchirawat et al, 2006Ruchirawat et al, , 2007Tuntawiroon et al, 2007), whereas data for nurseries, day care centers and PS environments are rather scarce (Eiguren-Fernandez et al, 2007;Oliveira et al, 2015Oliveira et al, , 2016aOliveira et al, , 2016b. Moreover, chil-dren interact with environment surrounding them in a unique way.…”
Section: Introductionmentioning
confidence: 99%
“…Whereas the levels reported Baxter et al (2014) are close to that value, the concentrations in the breathing zones 2.1 (0.1-6.7) 1.3 (0.1-4.0) 3.0 (0.9-5.6) 0.9 (0.0-3.4) of the studied subjects of this work were well below the recommended guideline. However, it is necessary to remark that Nap (as well as other light-molecular weight PAHs with 2-3 aromatic rings) is predominantly found in the gas phase (Oliveira et al, 2015b(Oliveira et al, , 2016b, which was not assessed in this work; thus the respective exposures of studied subjects at five fire corporations might be underestimated. Therefore, to adequately evaluate occupational exposure to PAHs (even during nonfires settings), future works should consider assessment of gaseous PAHs that are commonly not considered (Lui et al, 2017;Montaño-Soto et al, 2017;Oliveira et al, 2015a).…”
Section: Pah Levelsmentioning
confidence: 94%